Market Orientation: the Concept and Its Development - Mekoth, Nandakumar (Ushus Journal of Business Management, 2021)
The concept of market orientation has been one of the most discussed and researched topics in the last decade, This paper attempts to bring out the meaning, need and features of market orientation and the steps involved in its implementation. The paper identifies the relationship of various related concepts with the concept of market orientation. The paper also traces back the development of the field of market orientation through literature survey and identifies the distinct stages in the process of development.